Self-assessment of core clinical skills in medical graduates: medical interview, physician patient relationship and communication - Sogi, Cecilia (2006)
Objective: To assess the perception of medical graduates in regards to their training in medical interview, physician-patient relationship and communication skills. Materials and Methods: Applicants to a 2005-residency post at the Universidad Nacional Mayor de San Marcos participated in the study. The questionnaire was designed adapting three instruments. Validity and reliability studies were carried out. Results: A total of 917 graduates completed the questionnaire, 59% were male; 56% between 25-29 years old; 85% responded to having had training in core clinical skill, but various deficiencies were identified: a) clinical method; b) psychosocial data gathering; c) patient´s comprehension examination; d) emotions management; e) non verbal communication. The time as limiting factor for adequate relationship/communication with the patient was identified in respondents´ comments. Conclusion: Several deficiencies in core clinical skills were identified and should be considered in educational intervention programs.